A New 7-Level Symmetric Multilevel Inverter with Minimum Number of Switches. (29th August 2013) - Umashankar, S.; Sreedevi, T. S.; Nithya, V. G.; Vijayakumar, D.
Abstract : Though the multilevel inverters hold attractive features, usage of more switches in the conventional configuration poses a limitation to its wide range application. Therefore, a renewed 7-level multilevel inverter topology is introduced incorporating the least number of unidirectional switches and gate trigger circuitry, thereby ensuring the minimum switching losses, reducing size and installation cost. The new topology is well suited for drives and renewable energy applications. The performance quality in terms of THD and switching losses of the new MLI is compared with conventional cascaded MLI and other existing 7-level reduced switch topologies using carrier-based PWM techniques. The results are validated using MATLAB/SIMULINK.